2021
DOI: 10.1590/1982-0224-2020-0133
|View full text |Cite
|
Sign up to set email alerts
|

A cascade of dams affects fish spatial distributions and functional groups of local assemblages in a subtropical river

Abstract: Dams reduce the longitudinal connectivity of rivers and thereby disrupt fish migration and the spatial distribution of species, impacts that remain poorly studied for some Neotropical rivers from mega-diverse basins. We investigated the spatial distribution of fish species with different trophic and movement/reproductive/size characteristics to assess how functional groups have responded to a cascade of dams on the Uruguai River in southern Brazil. Fish abundance, biomass, and species composition were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Faucheux et al (2022) investigated longitudinal patterns in species richness across 16 reservoir cascades in North America and reported that various patterns existed including some that increased in an upstream direction in some basins and decreased in others, and some that simply remained constant throughout the basin. In South America, various authors (dos Santos et al, 2018; Loures & Pompeu, 2018; de Bem et al, 2021; Ganassin et al, 2021) have also reported gradients in species and trait richness that increased or decreased over reservoir cascades, depending on the basin. Factors that influence these apparently contradictory trends include regional climates and physical geography, distribution of tributaries and unimpounded reaches, and reservoir morphometry along the cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faucheux et al (2022) investigated longitudinal patterns in species richness across 16 reservoir cascades in North America and reported that various patterns existed including some that increased in an upstream direction in some basins and decreased in others, and some that simply remained constant throughout the basin. In South America, various authors (dos Santos et al, 2018; Loures & Pompeu, 2018; de Bem et al, 2021; Ganassin et al, 2021) have also reported gradients in species and trait richness that increased or decreased over reservoir cascades, depending on the basin. Factors that influence these apparently contradictory trends include regional climates and physical geography, distribution of tributaries and unimpounded reaches, and reservoir morphometry along the cascade.…”
Section: Discussionmentioning
confidence: 99%
“…These include limited information about species' traits, losing the interspecific variability often defined by more than just the observed traits, and associated reduced discriminatory power (Culp et al, 2011; Hoeinghaus et al, 2007; Lima et al, 2017; Verberk et al, 2013). Nevertheless, traits have been used successfully to study aspects such as effects of reservoir aging (dos Santos et al, 2017), oligotrophication (Ganassin et al, 2021), and responses of fish assemblages to impoundment (de Bem et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Species in feeding guilds that are associated with wider extensions of floodplain and that depend on allochthonous food resources provided by floodplain habitats (i.e. frugivores) are very likely to be affected by the modification of the flow regime due to hydropower damming of large rivers (Arantes et al, 2019; Correa et al, 2022; de Bem et al, 2021) and climate change (Herrera‐R et al, 2020). That is due to the disruption of the connectivity between the river and floodplains, which impedes the lateral exchange of nutrients and organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Free flowing rivers are hence fundamental not only for the species they support, but also for the evolutionary processes that they drive (Barbarossa et al 2020;Bem et al 2021;Vasconcelos et al 2021). Similarly, the conservation of regions of steep environmental gradients, which are expected to promote ecological speciation (Figure 4), is relevant from an evolutionary standpoint.…”
Section: Conservation Of Ecological and Evolutionary Processesmentioning
confidence: 99%